-(-15x)-3=

Simple and best practice solution for -(-15x)-3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-15x)-3= equation:


Simplifying
-1(-15x) + -3 = 0

Remove parenthesis around (-15x)
-1 * -15x + -3 = 0

Multiply -1 * -15
15x + -3 = 0

Reorder the terms:
-3 + 15x = 0

Solving
-3 + 15x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 15x = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 15x = 0 + 3
15x = 0 + 3

Combine like terms: 0 + 3 = 3
15x = 3

Divide each side by '15'.
x = 0.2

Simplifying
x = 0.2

See similar equations:

| xy=3x^2-6+y | | 9x+4x-6x-5=2 | | 108=12X^2 | | 3x+5x-6x-5=5 | | mx+4=3x-n | | 2x+9x-7x-5= | | p-8=24 | | e^5x+6=8e^3x | | 4sin^4x-1=0 | | 7(8x+2y)= | | 16=s+7 | | 10w-7-9w=1+7 | | 5x+7y=64 | | 2(6x+1)+4=12x | | 13(923x-76y)=100z | | 2xy+3x^2-60+y=6xy+x^2+150 | | 6(8X-1)-(6X+2)=(8X-3) | | 10x-1=58+(5x-9) | | W^2-10w*24=0 | | 10x-1=58 | | 5x+6y=-20 | | 33b+22a+44c=2581 | | the*crazy*dog=2500000000000 | | 22a+33b+44c=2581 | | 6c-3=-249 | | y(n+1)-3y(n+1)-4y(n)=0 | | 7b+9=-313 | | 1a+2b+3c=10 | | 2p+6=86 | | 2r^2-3r-4=0 | | 5z=90-2z | | 76+x+x+x=180 |

Equations solver categories